2009
DOI: 10.1243/09544100jaero545
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on a streamtraced hypersonic Busemann inlet

Abstract: Wind-tunnel testing and numerical simulation of a streamtraced hypersonic Busemann inlet were conducted at Mach 5.3 to investigate the flowfield characteristics and performance of this fixed-geometry inlet at conditions of design point. Wind-tunnel testing was also conducted at Mach 3.85 to investigate the starting and back-pressure limits of this inlet at conditions well below the design point. Results showed that the inlet could self-start at two tunnel conditions. At Mach 5.3, the inlet captured about 90 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Equation (6) shows that if the pressure ratios p 30 and total pressure recovery coefficients s 30 of any two streamtubes are equal, their contraction ratios are identical too. The property that any streamtube in a flow field has the same contraction ratio is defined in this paper as ''constant contraction.''…”
Section: Constant Contraction and Flow Uniformitymentioning
confidence: 99%
“…Equation (6) shows that if the pressure ratios p 30 and total pressure recovery coefficients s 30 of any two streamtubes are equal, their contraction ratios are identical too. The property that any streamtube in a flow field has the same contraction ratio is defined in this paper as ''constant contraction.''…”
Section: Constant Contraction and Flow Uniformitymentioning
confidence: 99%
“…) After Fourier transformation, Eq. 3 is changed into the spectral density matrix of (5) where S F(t) (ω) is the spectral density matrix of F(t) in Eq. 1,…”
Section: The Description Of Random Excitationmentioning
confidence: 99%
“…Experiment equipment is the ES-50000 electric vibration table and the acceleration sensor is installed the position of measurement point. The experiment parameter is shown in Table 1 [5,6]. The real object of this mechanism is shown in Fig.…”
Section: Random Vibration Experimentsmentioning
confidence: 99%
“…1 Since the sixties of last century, domestic and foreign researchers have done lots of work on hypersonic inward turning inlets, particularly the Busemann inlets. [2][3][4] Studies have shown that this type of inlet has advantages of higher capture flow and compression efficiency, smaller infiltration area, wider adaptability etc.…”
Section: Introductionmentioning
confidence: 99%